PENYULUHAN KEWAJIBAN PAJAK ORANG PRIBADI BAGI PARA SISWA YAYASAN PRIMA UNGGUL DI JAKARTA TIMUR - Widjaja , Djeni Indrajati (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Universitas Tarumanagara, 2024)
In recent years, businesses and activities that can be carried out by anyone who is creative and diligent can provide income. During the pandemic, in the midst of anxiety about a worrying new viral disease, conditions and the terms lock down, work from home, school from home have emerged, various creativity and new businesses or activities have emerged which are driven by young people and can provide income for them. These businesses are also known to have direct contact with millennials and Gen Z, such as jastip, selegram, YouTuber, tik toker, and so on. The students at YPU are mostly Gen Z and have creativity that can generate income. From the Fiscus perspective, this income is something that can be consumed and can increase wealth. So that activities that can generate income will be in contact with tax obligations. An introduction to tax obligations for those who have income is provided through online counseling with concise and precise explanations accompanied by example questions. This explanation was welcomed enthusiastically and increased the students' knowledge.